DETEKSI DINI SIMPTOM DEPRESI PADA REMAJA SMA NEGERI DI WILAYAH JAKARTA SELATAN - Idulfilastri, Rita Markus; Fransiska Angelika; Anastasya Dumyanti; Siti Bahiyah (Jurnal Bakti Masyarakat Indonesia, 2025)
Mental health is an important aspect of supporting the development of Indonesia's human resources, especially for the young population. Currently, there are many discussions about the behavior of school students that lead to depressive disorders. This PkM aims to detect depression using the SRED-7F instrument (Emotion Regulation Strategy with Simpton Depression-7Factor). The benefit for schools is to get recommendations for student assessment reports and at the same time get a mapping of students classified as depressed. PkM activities began with an application for permission to obtain student data from the Education Office Region I, South Jakarta. Data collection was carried out on January 21 and 22, 2025 and data from 238 students were obtained. The results showed that 18% of students indicated depression, 49% indicated but could still be overcome, and the rest (37%) did not indicate symptoms of depression. It is also obtained how students overcome depression, namely using adaptive emotional regulation and simultaneously suppressing maladaptive emotional regulation (33%); more use of adaptive emotional regulation but has not been able to suppress maladaptive emotional regulation (27%); more use of maladaptive emotional regulation but has not been able to use adaptive emotional regulation effectively (22%); not effectively using adaptive and maladaptive emotional regulation (18%). Suggestions for schools to conduct depression assessments for students on a regular basis including conducting training to improve the ability to develop emotion regulation strategies. ABSTRAK Kesehatan mental merupakan aspek penting mendukung pembangunan sumber daya manusia Indonesia, terutama bagi penduduk usia muda. Pada saat ini banyak pembahasan mengenai perilaku siswa sekolah yang mengarah pada gangguan depresi. PkM ini bertujuan melakukan pendeteksian depresi menggunakan instrumen SRED-7F (Strategi Regulasi Emosi dengan Simpton Depresi-7Faktor). Manfaat bagi sekolah mendapat rekomendasi laporan asesmen siswa dan sekaligus mendapatkan pemetaan siswa tergolong depresi. Kegiatan PkM diawali dengan permohonan izin mendapatkan data siswa dari Suku Dinas Pendidikan wilayah I, Jakarta Selatan. Pengambilan data dilakukan pada 21 dan 22 Januari 2025 dan diperoleh data dari 238 siswa. Hasil menunjukkan siswa terindikasi depresi sebesar 18%, terindikasi tapi masih dapat diatasi sebesar 49% dan sisanya (37%) tidak terindikasi gejala depresi. Diperoleh juga cara siswa mengatasi depresi yaitu menggunakan regulasi emosi adaptif dan secara bersamaan menekan regulasi emosi maladaptif (33%); lebih banyak menggunakan regulasi emosi adapatif namun belum dapat menekan regulasi emosi maladaptif (27%); lebih banyak menggunakan regulasi emosi maladaptif tapi belum dapat menggunakan regulasi emosi adaptif dengan efektif (22%); belum efektif menggunakan regulasi emosi adaptif dan maladaptif (18%). Saran bagi sekolah untuk melakukan asesmen deteksi dini depresi bagi siswa secara berkala termasuk melakukan pelatihan untuk meningkat kemampuan menyusun strategi regulasi emosi.